An experimental analysis of grandfathering versus dynamic auctioning in the EU ETS - Botelho, Anabela (2011)
Purpose – This study constitutes a first attempt to experimentally test the performance of a 100% auction versus a 100% free allocation of CO2 permits under the rules and parameters that mimic the EU ETS (imperfect competition, uncertainty in emissions' control, and allowing banking), with environmental targets more restrictive than the current ones but foreseeable for the near future. Methodology/approach – Two experimental treatments were run to achieve our goal. Both included the rules and the parameters that parallel the EU ETS structure, the only difference being the rule for the primary allocation of permits. Findings – Our experimental results indicate that the EU ETS has the potential to reduce CO2 emissions, achieving targets considerably more restrictive than the current ones at high efficiency levels, both with auctioned and free emission permits. Practical implications – Concerns about undue scarcity, and corresponding high prices, in secondary markets generated by a primary auction market are not warranted under the proposed dynamic auction format. This adds arguments favoring auctioning over grandfathering as the rule for the initial allocation of emission permits in the EU ETS. Originality/value of chapter – This study implements a theoretically appropriate auction format for the primary allocation of emission permits (the Ausubel (2004) auction) and incorporates a first attempt to include in the analysis measures of the risk preferences of subjects participating in emission permits experiments. These characteristics are for the first time implemented under a complex experimental design (including uncertainty of emission abatement, and banking), trying to parallel the EU ETS trading environment.